Versatile and efficient fabrication of signal “turn‐on” lateral flow assay for ultrasensitive naked eye detection of small molecules based on self‐assembled fluorescent gold nanoclusters‐antigen aggregates - Mengjia Chao; Shengmei Tai; Minxin Mao; Wenbo Cao; Chifang Peng; Wei Ma; Yongwei Feng; Zhouping Wang (Aggregate)
Abstract Fluorescence signal “turn‐on” lateral flow immunoassay (FONLFA) through nanomaterial labeled quenching fluorescent nanomaterial has shown significant potential for the detection of small molecules. However, the fluorescent nanomaterial immobilization on nitrocellulose (NC) membrane commonly requires tedious chemical modification and only a few combinations of fluorescence donor and quencher have been applied in FONLFA. In this work, bright fluorescent metal nanoclusters (Prot‐AuNCs) were prepared and self‐assembled into Prot‐AuNCs/antigen aggregates with three typical small molecule antigens, respectively. The aggregates can be readily immobilized on the surface of the NC membrane, indicating that this strip fabrication strategy has good versatility. Moreover, we evaluated the performances of this FONLFA platform by using carbendazim as a model target and investigated four typical nanomaterials as colorimetric nanoprobes and fluorescence quenchers. We found that all the nanoprobes demonstrated significantly improved naked eye detection sensitivity (vLOD) and limits of detection (LODs) in quantitative analysis. Among them, combing the Fe‐polydopamine nanoparticles as quencher with the above aggregates, the FONLFA in signal “turn‐on” mode achieved 200‐fold improved vLOD (0.05 ng mL−1) compared with conventional colorimetric AuNPs‐based lateral flow immunoassay (AuNPs‐LFA) (10 ng mL−1). In addition, the LOD in quantitative analysis also was improved by 22‐fold and the whole test process was completed within 10 min. With the advantages of efficient fabrication, extraordinary sensitization, and good biocompatibility, our FONLFA platform is expected to have great potential in the rapid detection of various small molecules.